Influence of the texture of compound feed in its nutritional use. 1. Effect of various binders on the digestibility, nutritive value and coefficients of growth efficiency of a diet in rats. - Pintor, Mª. Dolores; Boza, J.; Varela, G. (Ars Pharmaceutica (Internet), 1970)
We have carried out four tests of digestibility and coefficients of efficacy in the growth of rats, using a basic diet in the form of flour, granulated with the addition of bentonite, lignosulphonate or starch as binding substances in quantities of 2%, with the obpect of discovering the effect wich these aglutinants could have on digestibility and these coefficients.